1998
DOI: 10.1136/bmj.316.7135.937a
|View full text |Cite
|
Sign up to set email alerts
|

Future of preschool vision screening

Abstract: Should morphine or pethidine be given? Editor-Davies and Oni's review of the management of sickle cell disease 1 was published in the same issue of the BMJ as the evaluation by Fertleman et al of a fast track admission policy for children with sickle cell crises. 2 The review is based on the practice at the Central Middlesex Hospital, where pethidine has been associated with fits, and morphine is the preferred analgesic. 1 At the North Middlesex Hospital, only a few miles away, pethidine is evidently preferred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…The benefit of early detection and treatment also receives strong support from Williams et al (2002) who reported that at 7.5 years, amblyopia was significantly less prevalent in the intensively screened group than in the control group (0.6% v 1.8%), and from Kvarnstrom et al (1998) and Kvarnstrom et al (2001) who reported better visual outcomes when multiple early screenings take place. These results provide solid evidence for the view expressed by Simons (2005) and others (Williamson et al, 1995; Williams et al, 1998; Preslan and Novak, 1996, 1998) that amblyopia is more prevalent in socially disadvantaged and medically-underserved communities (see ‘Other Factors’ section below). However, it is noteworthy that even in populations that have access to screenings and therapy (e.g.…”
Section: Prevalencesupporting
confidence: 72%
“…The benefit of early detection and treatment also receives strong support from Williams et al (2002) who reported that at 7.5 years, amblyopia was significantly less prevalent in the intensively screened group than in the control group (0.6% v 1.8%), and from Kvarnstrom et al (1998) and Kvarnstrom et al (2001) who reported better visual outcomes when multiple early screenings take place. These results provide solid evidence for the view expressed by Simons (2005) and others (Williamson et al, 1995; Williams et al, 1998; Preslan and Novak, 1996, 1998) that amblyopia is more prevalent in socially disadvantaged and medically-underserved communities (see ‘Other Factors’ section below). However, it is noteworthy that even in populations that have access to screenings and therapy (e.g.…”
Section: Prevalencesupporting
confidence: 72%